A Theological Study of the Trinity The Neoplatonic Problem of "Una Substantia Tres Personae" and Its Relevance in Christian Education - Benyamin D.R. Mofu (Eduvest - Journal of Universal Studies, 2025)
This study aims to elaborate on Neoplatonic problems in the context of the concept and theological study of the Trinitarian doctrine and the Athanasian Creed (298-373) which states "Una Substantia Tres Personae", and explain its implications for Christian religious education. The approach used in this study is the literary method, which is particularly relevant for understanding and analyzing Neoplatonic thought in the context of the theology of the Trinitarian doctrine and the Athanasian Creed. Athanasius emphasized that although there are three persons in the Trinity, they share the same essence, which is "una substantia". The influence of Neoplatonism, which included ideas about the world of ideas and higher reality, created a complex framework of thought in understanding the relationship between God and creation. Therefore, Christian education needs to educate students about the history and context behind the doctrine of the Trinity, so that students can better appreciate the complexity and depth of this teaching. In addition, it also serves to avoid simplification that can reduce the meaning of the Trinitarian doctrine in daily life. Christian religious education should also include intertheological dialogue with a critical approach that encourages students to question and explore their own understanding.